Providing a Healthy Competition Environment between Organizational Structure Components in Improving Marketing Service Efficiency (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, scientific-practical suggestions and recommendations have been developed for improving the effectiveness of marketing service in industrial enterprises, ensuring a healthy competitive environment among the organizational structures, and improving the activities of the marketing service department. In addition, scientific research was conducted to ensure a competitive environment between departments within the organizational structure of enterprises and the marketing service department.